Handover methods between local emergency medical services and Accident and Emergency: is there a gold standard? A scoping review. - Guasconi, Massimo; Bonacaro, Antonio; Tamagnini, Emanuele; Biral, Silvia; Brigliadori, Linda; Borioni, Sabrina; Collura, Daniele; Fontana, Sara; Ingallina, Giulia; Bassi, Maria Chiara; Lucenti, Enrico; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2022)
Background: Pre-hospital emergency medical systems do not appear to work totally coordinated with Accident and Emergency (A&E). Often, patient admission to A&E is marked by scarce attention to the handover between the respective healthcare professionals. This phenomenon is potentially dangerous because it exposes patients to the risk of errors in a context where the patients’ critical or progressing conditions must not be worsened by avoidable errors of communication between professionals. Objectives: to describe the evidence concerning handover between local emergency medical services and A&E. Eligibility criteria: pre-hospital emergency medical and A&E professionals, setting defined as within A&E, articles on pre-hospital to A&E handover. Sources of evidence: PubMed and CINAHL Complete databases. Grey literature. Charting Methods: the results are displayed in tables according to ‘Title’, ‘Design’, ‘Country’, ‘Population’, ‘Concept’, ‘Context’ and ‘Results’. Results: 10 studies were included. The following themes emerged: communication and interpersonal issues, secondary risks, need for staff training, the use of structured methods, information technology support. Conclusions: There is a gap in the literature. Issues regarding communication, differing ideas of what should be considered as priority, interpersonal relationships and trust between staff working for different services emerge. Connected with this there are structural problems such as shortage of suitable spaces and lack of staff training. The use of structured mnemonic methods, including computerized ones, seems to improve the quality of handovers, but to date it has not been possible to establish which method would be better than another. Further studies are recommended.